2020
DOI: 10.1111/trf.16051
|View full text |Cite
|
Sign up to set email alerts
|

Blood use and transfusion needs at a large health care system in Washington state during the SARS‐CoV‐2 pandemic

Abstract: Background: This report evaluates hospital blood use trends during the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, and identifies factors associated with the need for transfusion and risk of death in patients with coronavirus 2019 (COVID-19). Methods: Overall hospital blood use and medical records of adult patients with COVID-19 were extracted for two institutions. Multivariate logistic regression models were conducted to estimate associations between the outcomes transfusion and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 23 publications
(38 reference statements)
2
18
0
Order By: Relevance
“…As a result of the spring lockdown lasting for 7 weeks, the output of this mode of donor drives declined by an average of 50% (range: 35%–61%). This reaction was also observed in several other countries 6,7,18,20 . The swing‐back of field donation activity was only partial in terms of number of field events (Figure 1(B) solid lines), however, event‐efficiency improved substantially with a total number of field donations close to our comparator value (Figure 1(A) middle curves).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As a result of the spring lockdown lasting for 7 weeks, the output of this mode of donor drives declined by an average of 50% (range: 35%–61%). This reaction was also observed in several other countries 6,7,18,20 . The swing‐back of field donation activity was only partial in terms of number of field events (Figure 1(B) solid lines), however, event‐efficiency improved substantially with a total number of field donations close to our comparator value (Figure 1(A) middle curves).…”
Section: Discussionsupporting
confidence: 85%
“…Similar trends have recently been described by others with reporting weekly hospital blood product utilization between the middle of February through the end of April 2020 in the Seattle area. There, more profound declines in PLT use were found compared to RBC, however, their comparator was less clearly defined 20 . In another report, an overall fall of 42% in daily transfusions was documented in the Baltimore area in March and April of 2020 and returning to normal in May but without comparing to similar unaltered time periods 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Our centers offer both adult and pediatric ECMO services, and ECMO use has been previously associated with blood product transfusions at other centers offering it, in particular RBCs and cryoprecipitate. 10,13 In one of these studies, 3 out of 128 (2.4%) COVID-19 inpatients required ECMO and all received transfusions. Communication and flexibility with our blood suppliers was critical to avoiding additional inventory shortages; during the peak of the pandemic, we communicated with our blood suppliers daily to inform them of our inventory needs and for them to update us on their available supply.…”
Section: Discussionmentioning
confidence: 99%
“…This can be very challenging at times when measures to contain an infectious outbreak substantially affect blood center operations and efforts to maintain sufficiency in other blood products. [52][53][54][55] Logistical issues such as delays in access to CP for clinical trials have been reported. 54,55 Conclusions CP may be of benefit for COVID-19, but more information on both efficacy and safety is needed.…”
Section: Implications For Blood Services and Blood Donorsmentioning
confidence: 99%